Hak Atas Satuan Rumah Susun Bagi Warga Negara Asing Berdasarkan Peraturan Pemerintah Nomor 18 Tahun 2021 - Kristhy, Mutia Evi; Aprilla, Astri Putri (Universitas Negeri Malang, 2022)
This study analyzed the rights to flats for foreign citizens based on Government Regulation Number 18 of 2021 and legal certainty in Government Regulation 18 of 2021. This study used a normative legal method with a statutory and conceptual approach. The provisions of Article 71 paragraph (1) letter b of Government Regulation Number 18 of 2021 regulated the right to apartment units for foreign nationals. As a result, foreign citizens could obtain use rights or building use rights on flats built on state land, land rights management, or property rights. However, government Regulation Number 18 of 2021 was considered unable to provide legal certainty because it was contrary to Law Number 5 of 1960 as a higher-level regulation. Article 37 of Law Number 5 of 1960 did not stipulate that foreign nationals could obtain building use rights as described in Article 71 paragraph (1) letter b of Government Regulation 18 of 2021.